(untitled) (International Educators Conference, 2025)
Acute intestinal obstruction (AIO) remains one of the most urgent and life-threatening conditions in abdominal surgery. The coexistence of diffuse liver diseases (DLD), such as chronic hepatitis and liver cirrhosis, significantly worsens the clinical course and surgical outcomes. Impaired detoxification, protein-synthesizing and coagulation functions of the liver increase the risk of postoperative complications, infectious processes, and mortality. In this regard, maintaining adequate liver function and providing targeted hepatoprotective therapy during the perioperative period becomes a critical factor in improving treatment results and prognosis in patients with AIO combined with DLD.